2008
DOI: 10.1177/1069072708317383
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy for Managing Work—Family Conflict

Abstract: The Self-Efficacy for Work—Family Conflict Management Scale (SE-WFC), developed in Israel, was designed to assess beliefs regarding one's ability to manage conflict between work and family roles. This study examined the factor structure, reliability, and validity of an English language version of the SE-WFC in a sample of 159 working mothers in the United States. Results indicated that the measure produced satisfactory estimates of internal consistency and test—retest reliability. It also correlated as expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This measure has been used in other studies with teachers (Barnabé & Burns, 1994;Klusmann et al, 2008). Previous research has established the job satisfaction scale as being reliable, with a reported Cronbach's alpha ranging from .77 to .86 (Barnabé & Burns, 1994;Hennessy & Lent, 2008;Klusmann et al, 2008;Munz, Huelsman, Konold, & McKinney, 1996;Wiley, 1987). Wiley (1987) also tested the validity of the subscale by exploring its relationships between job involvement and global life satisfaction and found that both were positively correlated (r = .54, p < .05 and r = .41, p < .05 respectively).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…This measure has been used in other studies with teachers (Barnabé & Burns, 1994;Klusmann et al, 2008). Previous research has established the job satisfaction scale as being reliable, with a reported Cronbach's alpha ranging from .77 to .86 (Barnabé & Burns, 1994;Hennessy & Lent, 2008;Klusmann et al, 2008;Munz, Huelsman, Konold, & McKinney, 1996;Wiley, 1987). Wiley (1987) also tested the validity of the subscale by exploring its relationships between job involvement and global life satisfaction and found that both were positively correlated (r = .54, p < .05 and r = .41, p < .05 respectively).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Work satisfaction was assessed using the three-item general work satisfaction items from the Job Diagnostic Survey (Hennessy 2005 ). Using a 7-point Likert scale, ranging from ‘strongly disagree’ (1) to ‘strongly agree’ (7), participating nurses were asked to indicate the extent to which they agreed with the three work satisfaction items.…”
Section: Methodsmentioning
confidence: 99%
“…Family satisfaction was assessed using a shortened 5-item version of the quite established Brayfield and Rothe’s (1951, cited in Hennessy 2005 ) work satisfaction scale. The version used was a modification by Hennessy ( 2005 ). In the modified version, the word ‘work’ was replaced with the term ‘family life’.…”
Section: Methodsmentioning
confidence: 99%
“…The findings have revealed that extrovert managers showing more corporation, agreement, and compromising. Hennessy and Lent (2008) explained that self-efficiency and conflict management have a direct association.…”
Section: Role Of Conflict Management Styles On Self-efficiency At Wormentioning
confidence: 99%